A mitochondrial retroplasmid integrates into mitochondrial DNA by a novel mechanism involving the synthesis of a hybrid cDNA and homologous recombination. - Chiang, C C (1994)
The Mauriceville and Varkud mitochondrial plasmids of Neurospora spp. are closely related, small circular DNAs that propagate via an RNA intermediate and reverse transcription. Although the plasmids ordinarily replicate autonomously, they can also integrate into mitochondrial DNA (mtDNA), yielding defective mtDNAs that in some cases cause senescence. To investigate the integration mechanism, we analyzed four cases in which the Varkud plasmid integrated into the mitochondrial small rRNA gene, three in wild-type subcultures and one in a senescent mutant. Our analysis suggests that the integrations occurred by the plasmid reverse transcriptase template switching between the plasmid transcript and internal sequences in the mitochondrial small rRNA to yield hybrid cDNAs that circularized and recombined homologously with the mtDNA. The integrated plasmid sequences are transcribed, presumably from the mitochondrial small rRNA promoters, resulting in hybrid RNAs containing the 5' segment of the mitochondrial small rRNA linked head-to-tail to the full-length plasmid transcript. Analysis of additional senescent mutants revealed three cases in which the plasmid used the same mechanism to integrate at other locations in the mtDNA. In these cases, circular variant plasmids that had incorporated a mitochondrial tRNA or tRNA-like sequence by template switching integrated by homologous recombination at the site of the corresponding tRNA or tRNA-like sequence in mtDNA. This simple integration mechanism involving template switching to generate a hybrid cDNA that integrates homologously could have been used by primitive retroelements prior to the acquisition of a specialized integration machinery.